The Effect Of Benefit Perception And Financial Literacy With Consumer Satisfaction As A Mediating Variable On Interest In Using Payment Systems Shopee Paylater - Febriyanthi, Putu Wina; Suarmanayasa, I Nengah; Trianasari (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Advances in technology have made many aspects of life easier, including in terms of payment systems and financial services. Paylater is one of the financial services offered by several e-commerce companies and has similarities with the banking credit system. The objectives of this study were (1) to examine the effect of perception of benefits on the interest in using Shopee PayLater payment methods; (2) to examine the effect of financial literacy on the interest in using Shopee PayLater payment methods; (3) to examine the effect of perception of benefits on Shopee PayLater consumer satisfaction; (4) to examine the effect of financial literacy on Shopee PayLater consumer satisfaction; (5) to examine the effect of consumer satisfaction on Shopee PayLater usage interest; (6) to examine consumer satisfaction mediate the effect of perception of benefits on interest in using Shopee PayLater; and (7) to examine financial literacy mediate the effect of perception of benefits on interest in using Shopee PayLater. This type of research used quantitative with a population of 3,117 students of the Faculty of economics class of 2023/2024, while the sample required 97 respondents, and the sampling technique used purposive sampling. The results showed that (1) perception of benefits has a significant positive effect on interest in using Shopee PayLater; (2) financial literacy has a significant positive effect on interest in using Shopee PayLater; (3) perception of benefits has a significant positive effect on consumer satisfaction Shopee PayLater; (4) financial literacy has a significant positive effect on consumer satisfaction Shopee PayLater; (5) consumer satisfaction has a significant positive effect on interest in using Shopee PayLater; (6) consumer satisfaction can mediate the perception of benefits to the interest in using Shopee PayLater; and (7) consumer satisfaction can mediate financial literacy to the interest in using Shopee PayLater.